Pengaruh Keterlibatan Mahasiswa dalam Program Green Accounting Society Terhadap Kesadaran Mereka Terhadap Isu Lingkungan - Amelia Rahmayani; Rismawati; Zikra Supri (PT Bone Jaya Kreatif, 2024)
This study aims to determine whether student participation in the green accounting society program can affect environmental awareness. This research method uses quantitative methods using purposive sampling method with a sample of respondents selected purposively. Data were collected through a questionnaire which included variables of student participation, Green Accounting Society, and environmental awareness. The population in this study were 7th semester class A students at the Faculty of Economics & Business, Universitas Muhammadiyah Palopo. Data analysis techniques were carried out using the Statistical Package for the Social Sciences (SPSS) 25th edition application. The results of this study indicate that student participation has no significant effect on environmental awareness, while the green accounting society has a significant effect on environmental awareness.